2014
DOI: 10.1007/s10548-014-0410-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution of Neural Activity Underlying Auditory Discrimination of Frequency Increase and Decrease

Abstract: Discriminating a direction of frequency change is an important ability of the human auditory system, although temporal dynamics of neural activity underlying this discrimination remains unclear. In the present study, we recorded auditory-evoked potentials when human subjects explicitly judged a direction of a relative frequency change between two successive tones. A comparison of two types of trials with ascending and descending tone pairs revealed that neural activity discriminating a direction of frequency c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Getzmann et al ( 2013 ) reported further evidence that corroborates our findings, demonstrating that providing training in pitch discrimination with background noise to older participants improved their performances on the task and yielded stronger P2 amplitudes (Getzmann et al, 2013 ). A recent study on auditory discrimination reported that fronto-central P2 was related to judgment of the auditory frequency process (Noguchi et al, 2015 ). One could argue that older participants’ lower performances on the spatial discrimination task in this study was due to their deteriorated audial and visual senses.…”
Section: Discussionmentioning
confidence: 99%
“…Getzmann et al ( 2013 ) reported further evidence that corroborates our findings, demonstrating that providing training in pitch discrimination with background noise to older participants improved their performances on the task and yielded stronger P2 amplitudes (Getzmann et al, 2013 ). A recent study on auditory discrimination reported that fronto-central P2 was related to judgment of the auditory frequency process (Noguchi et al, 2015 ). One could argue that older participants’ lower performances on the spatial discrimination task in this study was due to their deteriorated audial and visual senses.…”
Section: Discussionmentioning
confidence: 99%
“…Electrodes C3 and C4 were used to represent activity in the auditory cortex (Carpenter and Shahin, 2013;Noguchi, Fujiwara and Hamano, 2015). Theta-band (4 ~ 6 Hz, corresponding to stimulus repetition rate of ~ 5 syllables per second) phase-locking values (PLVs) were measured.…”
Section: Cortical Responsesmentioning
confidence: 99%
“…Several cortical components in this time-range, mentioned above as biased by FC direction, may be involved. An amplitude advantage for Up in the cortical P1 is seen already~50 ms pOnst (Noguchi et al, 2015); a FC-direction latency bias in the N100m is seen at 85 ms pOnst (Pardo & Sams, 1993). Also the N100 amplitude bias for FRQ rise, at 115 ms pOnst (Maiste & Picton, 1989), could be involved in our effect at 160 ms, if 45 extra ms suffice for its mediation to distal muscles.…”
Section: Routesmentioning
confidence: 65%
“…Some LLRs reveal FC direction bias, mostly of EEG amplitude, not latency. The P1 component (at 50 ms latency) during FC direction discrimination in discrete tones is larger in rise vs fall (Noguchi, Fujiwara, & Hamano, 2015). Unattended deviant-direction rising glides (vs falling) elicit earlier the N100m component (85 vs 93 ms; Pardo & Sams, 1993); rising glides elicit larger N100 (at 115 ms; Maiste & Picton, 1989) and larger N100-P200 (Wang, Tan, & Martin, 2013).…”
Section: Verifying Specificity Of Response To Frequency By Comparisonmentioning
confidence: 88%